Primary malignant melanoma of the female urethra: A rare case report - Anahita Ansari Djafari; Mohammad Seifi Poor; Sina Samenezhad; Reza Nicknama; Azadeh Rakhshan (Urology Case Reports, 2025)
A 61y/o woman who presented with a dark, bleeding mass at the urethral meatus, accompanied by dysuria and significant weight loss. Initial diagnosis by a GP suggested a urethral caruncle. Imaging revealed a urethral mass, which was surgically excised. Histopathological examination confirmed the diagnosis of malignant melanoma. Despite complete surgical resection, follow-up imaging 6 months later revealed widespread metastases. She was referred for systemic and immunotherapy. This case underscores the importance of considering urethral melanoma in the differential diagnosis of urethral masses, especially when the presentation mimics benign conditions. Early recognition, thorough staging and prompt intervention are crucial for improving outcomes.